Corporate Governance Mechanisms and TaxAvoidance Behavior: The Role of Firm Profitability - Kasir; Kosadi, Ferry; Arismutia, Salza Adzri; Eleanor, Edelweiss (Communication in Research and Publications (CRP), 2025)
This study aims to analyze the effect of corporate governance on tax avoidance and profitability as a mediating variable in property and real estate. The results show that institutional ownership and the composition of the independent board of commissioners affect profitability and simultaneously institutional ownership and the composition of the independent board of commissioners and profitability affect tax avoidance. Institutional ownership affects profitability and profitability affects tax avoidance. However, the composition of the independent board of commissioners does not affect profitability and neither institutional ownership nor the composition of the independent board of commissioners has an effect on tax avoidance. Profitability can mediate institutional ownership on tax avoidance. Independent board composition on tax avoidance cannot be mediated by profitability. The mediating variable of profitability on corporate governance and tax avoidance with the research location in the property and real estate sector is the originality of this research. The practical implications of this research illustrate in the property and real estate sector, that increasing the level of profit will be influenced by corporate governance which has an impact on the level of tax avoidance. As well as a reference for the tax authorities to make policies.